Effect of Organizational Culture, Organizational Commitment and Self Effication of Teacher Performance Medium Religious Education Province of Central Java (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to test the influence of ( 1) organizational culture variables on teacher performance; (2) the variable organizational commitment to teacher performance; and (3) self- efficacy variable on teacher performance. This research deg using the positivistic quantitative method, the sample in this study 53 res}xindents, using path analysis. The sampling technique used is probability sampling by applying proportionate stratified random sampling. The results of the analysis showed that there are several influences: ( I ) positive and significant influences between organizational culture variables on teacher performance by 43.8°/c; (2) positive and significant between the variable organizational commitment to teacher performance by 25.8°/c; (3) positive and significant between the variable self-efficac y on teacher rinance by 60.6°/c. The analysis results can be concluded that the variables of organizational culture, organizational commitment, and efficacy have a positive and significant effect on the performance of middle-level Buddhist education teachers in Central Java Province.